Low serum triiodothyronine and potassium levels are associated with increased risk of eclampsia among women in the Eastern Cape Province of South Africa - Charles Bitamazire Businge; Benjamin Longo-Mbenza; Andre Pascal Kengne (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: There is paucity of data on the relationship between thyroid hormones, potassium and eclampsia. Moderate-to-severe iodine deficiency that worsens during pregnancy leads to decreased thyroid hormone output and bioavailability to the brain. Apart from metabolic functions, T3 and T4 are essential fast acting cytosolic and synaptosomal neural transmitters that also regulate neuronal excitatory-inhibitory mechanisms. T3 also regulates the Na + -K + -ATPase pump that maintains the membrane ionic gradient. Hence altered serum potassium, thyroxine and triiodothyronine levels could increase the risk of eclamptic seizures. Methods: Forty-five women with eclampsia, 45 severe preeclampsia and 90 normotensive pregnant controls were enrolled into this study. Levels of thyroid hormones, thyroglobulin and urine iodine concentration (UIC) were measured and compared between the three groups. Results: Eclamptic participants had significantly lower median serum potassium (K), triiodothyronine (FT3), urinary iodine concentration (UIC) but higher serum thyroglobulin (Tg) (K = 3.7 mmol/L; FT3 = 3.8 pmol/L; UIC = 69.5 μg/L; Tg = 39.0 μg/L) than normotensive pregnant controls (K = 4.3 mmol/L; T3 = 4.7 pmol/L; UIC = 169.5 μg/L; Tg = 19.5 μg/L) and participants with severe preeclampsia (K = 4.2 mmol/L; T3 = 4.4 pmol/L; UIC = 95.7 μg/L; Tg = 22.4 μg/L), p < 0.05. Low UIC, low serum T3 and potassium and elevated Tg were independent predictors of eclampsia. Conclusions: Women with iodine deficiency in pregnancy may be at increased risk of eclampsia secondary to the ensuing rapid peripheral turnover of thyroid hormones leading to hypothyroxinaemia and reduced triiodothyronine bioavailability to the central nervous system that can be exacerbated by hypokalaemia.